Metoclopramide-Induced Acute Dystonic Reactions May Be Associated With the CYP2D6 Poor Metabolizer Status and Pregnancy-Related Hormonal Changes - Chua, Eng Wee; Harger, Simon P.; Kennedy, Martin A. (Frontiers in Pharmacology, 2019)
We report two cases of metoclopramide-induced acute dystonia in pregnant women and consider the role of genetic variation in the pathogenesis of the adverse effect. By whole-gene sequencing, we found that both women were CYP2D6 poor metabolisers. We theorise that CYP2D6 governs the risk of metoclopramide-related acute dystonia through its role in the synthesis of serotonin, which inhibits the dopamine tone. The effect of CYP2D6 poor metabolism is exaggerated by rises in the oestrogen levels during pregnancy, as the hormone augments dopamine sensitivity. Together, the two factors may create a hyper-dopaminergic state that is easily upset by metoclopramide, resulting in acute dystonia.